THE LEGAL PROTECTION FOR APPRAISERS: PREVENTION OF LEGAL CASES AFFECTING APPRAISERS - Santoso, Ruddy Tri; Widiastuti, Arum (Jurnal Pembaharuan Hukum, 2024)
The aims of this study is to determine the legal protection for appraisers in carrying out professional risks in accordance with regulations. The research method used normative juridical research results stated that the greatest risk faced by appraisers in Indonesia was in the field of land acquisition for public interest which was systemic and involves appraisers as the party most responsible for state losses caused by the issuance of the compensation value opinion, it was appropriate for the appraiser profession to obtain legal protection in the form of the issuance of the Appraisal Law to protect their work as a profession. Novelty in this study, the researcher proposes the importance of ratifying the Appraisal Law to minimize the risk of appraisers facing the law, both criminally and civilly. As a legal umbrella, the Appraisal Profession also regulates legal governance within the Appraisal Profession like other professions in Indonesia, including if there is a dispute, both criminally and civilly. The formation of the Appraisal Supervisory Board is a proposal so that violations of the Appraisal Standards can be implemented through an ethics hearing first by this body before reaching the inquiry and investigation stage, both civil and criminal.